Targeting metzincins to mitigate jellyfish blooms: a novel approach for conservation - Liu, Xuecun; Peng, Xiao; Wang, Jingqiang; Ju, Shuhui; Sun, Qing; Ji, Wensai; Hua, Xiaoyu; Zhang, Haiyan; Höfer, Juan; Pozzolini, Marina; Xu, Shuogui; Ma, Xueqi; et al. (Frontiers in Marine Science, 2025)
IntroductionThe modification of the marine ecological environment has led to the frequent occurrence of jellyfish blooms, causing global hazards. The budding reproduction of jellyfish polyps is a critical factor in their population size, yet there is limited understanding of the molecular mechanisms involved in this process. This study aims to explore the intrinsic regulatory factors of the budding of jellyfish Aurelia coerulea (A. coerulea) polyps from the perspective of jellyfish biotoxin and to develop new strategies for the management of jellyfish abundance.MethodsThe main biological toxins of the A. coerulea polyp were screened through the integrated analysis of transcriptomic and proteomic data. The broad-spectrum metalloproteinase inhibitor, ethylenediaminetetraacetic acid (EDTA), was employed to treat polyps for observing its effect on the budding of A. coerulea polyps. Through conducting the detection of metzincin proteolytic activity, molecular docking and kinetic analysis, as well as transcriptomic analysis and RT-qPCR verification before and after EDTA treatment of the polyp, the key biological toxins and the mechanisms influencing polyp budding were clarified.ResultsFour types of the metzincin family of metalloproteinases constituted the main biotoxins in the A. coerulea polyp. Among them, astacins (NAS) were the predominant metzincins of the A. coerulea polyp. We discovered that EDTA significantly inhibited the activity of metzincins and the budding of A. coerulea polyps. EDTA was capable of stably binding to the zinc-binding active sites of the four major types of metzincins in the A. coerulea polyp and could down-regulate the expression levels of key metzincin molecules and enrich multiple pathways related to development.ConclusionThis study elucidates the effects of metzincins on the budding of jellyfish polyps, providing a potential target for mitigating jellyfish blooms.